Emergence of carbapenem-resistant ST131 Escherichia coli carrying blaOXA-244 in Germany, 2019 to 2020 - Welker, Sybille; Boutin, Sébastien; Miethke, Thomas; Heeg, Klaus; Nurjadi, Dennis (Eurosurveillance, 2020)
The dissemination of carbapenem-producing Gram-negative bacteria is a major public health concern. We report the first detection of OXA-244-producing ST131 O16:H5 Escherichia coli in three patients from two tertiary hospitals in the south-west of Germany. OXA-244 is emerging in Europe. Because of detection challenges, OXA-244-producing E. coli may be under-reported. The emergence of carbapenem resistance in a globally circulating high-risk clone, such as ST131 E. coli is of clinical relevance and should be monitored closely.